Comparison between species and cultivars in the genus Lotus - Paim, Nilton Rodrigues; Riboldi, João (Pesquisa Agropecuaria Brasileira, 1991)
Seven cultivars of the species Lotus corniculatus L. cv. San Gabriel, cv. El ganador and EEA-Population; Lotus subbiflorus cv. El Rincón; and Lotus uliginosus Schkuhr. cv. Maku, EMPASC - Selection and EEA-Population, were evaluated as dry matter yield in association with spontaneous species, in the area (white clover, grasses and weeds), at the Agronomic Experimental Station of the Federal University of Rio Grande do Sul (UFRGS), Southern Brazil, from June, 1987 to January, 1989. Seven harvests were done in the blooming stage of the Lotus species, the mixture components were separated in Lotus, white clover, grasses and weeds as a botanical composition. The cultivars of L. corniculatus were superior, in dry matter yield, as individual components and in the mixtures comparing to others species. Dry periods during the evaluation caused dry matter yield reductions in some harvests.
Keywords: Lotus corniculatus; Lotus subbiflorus; Lotus uliginosus; dry matter yield; cultivars